EXAMINING THE QUALITY OF BANKING SERVICES THROUGH CUSTOMERS’ EXPERIENCE OF THE SERVICE: A REVIEW STUDY - Amodah Obaid Hussein (Scholar Express Journals, 2025)
The purpose of the current research is to identify the role of previous literature in examining the quality of banking services (QBS) through the customer experience of service, as the (QBS)represents a key pillar in the academic and administrative literature in particular. The importance of banks is increasing by meeting all the requirements and needs of customers, as this represents one of the important elements through which banks seek to improve the quality of their services and meet the desires of customers, thereby achieving an acceptable level of satisfaction and loyalty. Based on this, previous studies have shown that the customer experience is an important element in measuring the (QBS)because it focuses on the impressions and feelings of customers during their service interactions with the bank. From this perspective, the current research has yielded a set of results, the most significant of which is that previous studies concentrated on understanding the feelings and needs of customers in a manner that guides banks towards gaining customer satisfaction and enhancing their loyalty, in order to distinguish the bank's services and thus improve (QBS), which in turn leads to an enhancement of the bank's reputation. This, in turn, contributes to the fulfilment of the needs and desires of customers.
Keywords: Services; Quality of Banking Services; Customer experience